Of "Women" and "Relationships" in Contemporary Bengali Cinema: Rituporno Ghosh's Oeuvre. Issue 2 (1st September 2002) - Mandal, Somdatta
He explores human relationships with a rare sensitivity. In all his films he handles human frailties with tenderness and understanding, humor and irony. It is this quality that won the young Bengali director Rituporno Ghosh, laurels for all the seven films he's made till date. In less than a decade, he has acquired a reputation that takes him far beyond his immediate area of creative operation in West Bengal. A simple storyline and superb acting make his movies special.As his films revolve around relationships, they are emotionally gripping and do not need the props of songs and dance.